2018
DOI: 10.1051/e3sconf/20183402034
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hazardous waste landfill leachate using Fenton oxidation process

Abstract: The efficiency of Fenton’s oxidation was assessed in this study for hazardous waste landfill leachate treatment. The two major reagents, which are generally employed in Fenton’s process are H2O2 as oxidizing agent and Fe2+ as catalyst. Batch experiments were conducted to determine the effect of experimental conditions viz., reaction time, molar ratio, and Fenton reagent dosages, which are significant parameters that influence the degradation efficiencies of Fenton process were examined. It was found that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Singa et al [40] observed that the maximum COD removal from landfill leachate by using photo Fenton was 68% under optimum operating conditions. Also, Singa et al [41] found that under favorable experimental conditions, maximum COD removal from landfill leachate by using Fenton process was 56.49%. Sruthi et al [42] indicated that heterogeneous Fenton process was capable of removing 88.6% COD from landfill leachate at the optimal conditions.…”
Section: Response Optimisation and Validation Of The Experimental Modelmentioning
confidence: 99%
“…Singa et al [40] observed that the maximum COD removal from landfill leachate by using photo Fenton was 68% under optimum operating conditions. Also, Singa et al [41] found that under favorable experimental conditions, maximum COD removal from landfill leachate by using Fenton process was 56.49%. Sruthi et al [42] indicated that heterogeneous Fenton process was capable of removing 88.6% COD from landfill leachate at the optimal conditions.…”
Section: Response Optimisation and Validation Of The Experimental Modelmentioning
confidence: 99%
“…UV radiation improves the usage of H2O2 concentration and speeds up the photolysis process on each small organic molecule, but the visible light photo Fenton process requires a long processing time and higher energy consumption. Using 14 W UV lamps at 1.1 g/L Fe ion and 5.5 g/L H2O2 concentration, 84.43% of COD and 92.54% of total PAHs were removed from landfill leachate wastewater (Singa et al, 2018). The three treatment methods virtually always used the ideal Fenton dose concentration.…”
Section: Comparative Analysis Ofmentioning
confidence: 99%
“…Industries employ different techniques to dispose of different types of organic wastes. Organic waste is considered dangerous for several reasons, which include, but are not limited to, its non-biodegradability, chemical inertness, and bioaccumulation in the human body (Ahmed et al, 2011;Papić et al, 2009;Singa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%